Pengaruh Kompetensi, Disiplin Pegawai, dan Lingkungan Kerja Fisik terhadap Kualitas Pelayanan Pegawai - Wakhidah, Luthfiana Nurul; Pramusinto, Hengky (Business and Accounting Education Journal, 2020)
Public service is an activity or a series of activities in the framework of fulfilling service needs in accordance with statutory regulations for every citizen and resident of goods, service, and or administrative services provided by public service providers. This study aims to determine the simultaneous and partial influence between employee competency, employee discipline, and physical work environment on the service quality of Kendal Regency’s Population and Civil Registration Service. The population in this study were service user in the Kendal Regency Population and Civil Registry Service 115 respondents analyzed as samples using the iteration formula. Data collection methods were done by questionnaires, observation, interviews, and documentation. Data were analyzed by multiple regression analysis and percentage descriptive analysis. The result of this study indicate that employee competency, employee discipline, and physical work environment have a positive and significant effect on the service quality. Employee competency have a positive and significant effect on the service quality, employee discipline have a positive and significant effect on the service quality, and physical work environment have a positive and significant effect on the service quality.